c - 9 (b, 2006)
Articles on the role of naval operations and naval battle groups involved in guerilla warfare in the 1971 independence war of Bangladesh.
Includes bibliographical references (p. [272]).
In Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Naval operations; Bangladesh -- History -- Revolution, 1971 -- Commando operations; Bangladesh -- History -- Revolution, 1971